Photosensitizing Properties of Alkynylrhenium(I) Complexes [Re(–C≡C–R)(CO)3(N∩N)] (N∩N = 2, 2′‐bipy, phen) for H2 Production (Eur. J. Inorg. Chem. 19/2014). Issue 19 (July 2014) - Oberholzer, Miriam; Probst, Benjamin; Bernasconi, Dominik; Spingler, Bernhard; Alberto, Roger
Abstract : The cover picture shows the reduction of protons by illumination of a catalytic mixture containing a cobalt‐based water‐reduction catalyst (WRC), a rhenium(I)–alkynyl photosensitizer, a proton source (H + ), and a sacrificial electron donor (D/D + ). The final product, hydrogen gas, stores the energy of light in its chemical bond. Their electrochemical and luminescence properties make alkynylrhenium(I) complexes excellent photosensitizers for artificial photosynthesis. In this study, various Re I –alkyne complexes were prepared, characterized, and subjected to photocatalytic proton reduction experiments. Details are discussed in the article by R. Alberto et al. onp. 3002 ff . For more on the story behind the cover research, see theCover Profile .